2017
DOI: 10.1590/s0102-053620170212
|View full text |Cite
|
Sign up to set email alerts
|

Tomato fertigation with dairy cattle wastewater

Abstract: The use of wastewater in the fertigation of agricultural crops increases productivity and product quality, and contributes to reduce environmental pollution. In this work, the objective was to evaluate how the use of dairy cattle wastewater (DCWW) in the fertigation of tomatoes affected production and productivity, as well as foliar nutritional contents, in an organic farming system. Treatments consisted of six nitrogen doses (0, 50, 100, 200, 300 and 400%), having N recommendation for tomato (100 kg/ha) as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the study developed by Jorge et al (2017), the authors concluded that the use of DCW fertigation for tomato cultivation demonstrated that there was an increasing linear effect on production, on accumulated productivity and on the accumulation of nutrients in the leaves as a function of the DCW concentration, and that the highest weekly and aggregated yield of tomatoes, as well as the highest leaf nutrient content, were observed when 400% of the nitrogen concentration recommended for tomatoes was used. However, the authors still indicated that nitrogen fertilization must be carried out in the organic cultivation of tomatoes, which can be done through DCW fertigation, but that it must be supplemented in mineral form, in order to provide the adequate amount of phosphorus and potassium for the plants.…”
Section: Soil Fertilitymentioning
confidence: 99%
“…In the study developed by Jorge et al (2017), the authors concluded that the use of DCW fertigation for tomato cultivation demonstrated that there was an increasing linear effect on production, on accumulated productivity and on the accumulation of nutrients in the leaves as a function of the DCW concentration, and that the highest weekly and aggregated yield of tomatoes, as well as the highest leaf nutrient content, were observed when 400% of the nitrogen concentration recommended for tomatoes was used. However, the authors still indicated that nitrogen fertilization must be carried out in the organic cultivation of tomatoes, which can be done through DCW fertigation, but that it must be supplemented in mineral form, in order to provide the adequate amount of phosphorus and potassium for the plants.…”
Section: Soil Fertilitymentioning
confidence: 99%
“…Several researches have pointed out the possibility of irrigation of several plant species with poor quality water, being a widely studied practice and recommended by several researchers and water managers. From a nutritional point of view, studies have shown positive effects of irrigation with high salinity water, such as sewage, on the production and productivity of vegetables, proving the fertilizing effect of wastewater in numerous studies and in various cultures such as sunflower (Santos Júnior et al, 2014;Oliveira et al, 2017), pepper (Silva et al, 2019), melon (Costa et al, 2014), corn (Malafaia et al, 2016), tomato (Jorge et al ., 2017) and watermelon (Salgado et al, 2018).…”
Section: Introductionmentioning
confidence: 99%